Modelling and Investigation of the Dynamic Behavior of a Penny-Shaped Interface Crack in Piezoelectric Bimaterials - Yani Zhang; Junlin Li; Di Liu; Xiufeng Xie (Advances in Mathematical Physics)
In this section, the dynamic propagation behavior of a penny-shaped interface crack in piezoelectric bimaterials is analyzed. The objective of this paper is to use the boundary conditions of the penny-shaped interface crack to study the dynamic propagation of the crack under the action of load, so as to provide some valuable implications for the fracture mechanics of the piezoelectric bimaterials and simulate the interface crack between piezoelectric bimaterials, it is necessary to establish a suitable model and give appropriate boundary conditions according to the actual situation. The elastic displacement and potential equations are constructed according to the structural characteristics of the circular crack. In the case of a given displacement or stress, the Laplace transform and Hankel transform are used to simplify the problem into an integral equation with unknown functions. According to the boundary conditions, the corresponding unknowns are obtained, and the closed solution is derived. The results show that the fracture toughness of a penny-shaped interface crack in piezoelectric bimaterials is related to the thickness of the material, the impact time, the material characteristics, and the electric field. At the same time, it can be found that different materials have different roles in the crack propagation, so it is very important to study the crack opening displacement (COD) intensity factor of the crack for safety design.